Bionanoconjugates of tyrosinase and peptide-derivatised gold nanoparticles for biosensing of phenolic compounds - Cortez, J (2011)
Bionanoconjugates of the enzyme tyrosinase (TYR) and gold nanoparticles (AuNPs) functionalised with a peptide (CALNN) were produced in solution and characterised. The formation of stable TYR-AuNP:CALNN bionanoconjugates (BNCs) was supported by a decrease of the surface charge of the BNCs as determined by zeta-potential and an increase in hydrodynamic diameter as determined by Dynamic Light Scattering (DLS). UV/Vis studies of pH-induced aggregation revealed distinct protonation patterns for the BNCs when compared with AuNP:CALNN alone, further substantiating BNC formation. Activity studies of the BNCs for the reduction of di-phenols in solution indicated that TYR not only remains active after conjugation, but interestingly its activity in the BNCs is higher than for the free enzyme. In conclusion, AuNP:CALNN can provide a suitable platform for the immobilisation of TYR, leading to BNCs with increased enzyme activity and a wider pH working range, with promising uses in electrochemical biosensors for the detection of mono- and di-phenolic compounds.